Capital flows to Asia and Latin America: Does institutional quality matter?. (1st April 2019) - Arya, Vandana; Banerjee, Rajabrata; Cavoli, Tony
Abstract: Using a sample of 28 emerging market economies from Asia and Latin America spanning 1990–2013, we show that the marginal effect of capital flows on growth is positive and contingent on the threshold level of institutional quality (IQ). The conditional effect of capital flows holds for both the income per capita growth and total factor productivity (TFP) growth. We also determine the different threshold levels of IQ at which the marginal effect of capital flows is positive. The overall level of IQ in the Asian countries is superior to the Latin American countries and requires a lower threshold level to exert any positive effect. While the same conditional effect of IQ holds in Latin America for TFP growth, this effect is reversed in Asia. For very high levels of IQ (91st percentile), the marginal effect of capital flows on TFP growth in Asia is almost negligible. The marginal effects also vary based on the composition of capital flows in each region.